Cyclodextrin‐Clathrated Limonin Suppresses Diet‐Induced Obesity in Mice. Issue 2 (22nd July 2013) - Halder, Debasish; Das, Nando Dulal; Jung, Kyoung Hwa; Choi, Mi Ran; Kim, Moo Sung; Lee, Sang Rin; Chai, Young Gyu
Abstract Limonin (Lim) is a white crystalline substance usually found in orange and lemon seeds. In this paper, we report the antiobesity effects of cyclodextrin (CD)‐treated Lim along with naringenin (Ng) and hesperetin (Hes). We demonstrated that Lim, Ng and Hes decreased cell viability in 3T3‐L1 preadipocyte cells. Lim, Ng and Hes inhibited the adipocyte differentiation in response to adipogenic inducers. The evidence for this inhibition included fewer Oil Red O positive droplets and a decreased expression of the adipocyte‐specific gene PPARγ2. In animal studies, Lim‐, Hes‐ and combination‐treated mice gained less body weight than control mice did. The plasma triglyceride and cholesterol levels were significantly reduced by Lim and the other substances. Furthermore, Lim increased the mRNA levels of lipid metabolism‐related genes, including Acox1, UCP2 and CPT1 in the liver. This study suggests that CD‐treated Lim prevents diet‐induced obesity in mice by inducing lipid metabolism‐related genes in the liver. Practical Applications Limonin (Lim) is a limonoid that has a bitter taste and is a water‐insoluble substance found in citrus fruits. It has several important biological properties. Citrus Lim does not dissolve in water, which makes it unsuitable for use in oral preparations. In the present study, we used a cyclodextrin‐treated Lim that is very easily dissolved in water. In this report, we demonstrated the anti‐adipogenic effects of citrus Lim in 3T3‐L1 preadipocyte cells. We also used cyclodextrin‐clathrated Lim, naringenin and hesperetin to examine the hypocholesterolemic activities in mice. The results from our study showed that Lim and these two flavonoid‐related compounds can be used to develop oral preparations that may have possible lipid‐lowering properties and may be able to reduce diet‐induced obesity.